PENGGUNAAN MEDIA KOKORU DALAM MENINGKATKAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI RA RAHMAH EL YUNUSIYYAH PADANG PANJANG - Mardiwi, Mardiwi; Kardi, Julis; Lestari, Mega Cahya Dwi (PSGA LP2M IAIN Pontianak, 2024)
Children's Fine Motor Skills at RA Rahmah El-Yunusiyyah are not optimal in their fine motor stages. Children are not able to fold with many patterns, if the folds are smaller, the child is not able to imitate them. The purpose of this study is to determine the implementation of the use of Kokoru media in improving Fine Motor Skills of children aged 5-6 years at RA Rahmah El-Yunusiyyah Padang Panjang. The method used in this study is Mix Method, which is a type of Classroom Action Research (PTK) research that uses two cycles in carrying out Kokoru media. The response in this study was children after 5-6 years at RA Rahmah El-Yunusiyyah Padang Panjang, in the even semester of 2023/2024. There are 11 children consisting of 5 girls and 6 boys. The data collection techniques in this study are observation and documentation. The results of this study conclude that kokoru activities can improve children's fine motor skills. In the first cycle, 3 meetings were held, in the first meeting of 28%, the second meeting of 36%, and the third meeting of 47%. In the second cycle, the first meeting was 58%, the second meeting was 72%, and the third meeting was 87%. Meanwhile, teacher observation was carried out in the first cycle of the first meeting of 41%, the second meeting of 47%, and the third meeting of 56%. In the second cycle, the first meeting was 69%, the second meeting was 88%, and the third meeting was 94%.Keywords: Kokoru Media, Increase, Children’s Fine Motor Skills.